The museum can be visitor-centered: an intern's reflection. Issue 2 (4th March 2018) - Woodruff, Anthony
Abstract: Within a personal narrative reflection method and social constructivism theory, a former intern reflects on their time at The Ringling Museum in Sarasota Florida. The article focuses on the intern's experience, which consisted of several roadblocks and high points. Much of these situations presented themselves within a context at odds with the intern's former teaching experiences and learning experiences within his own graduate program. Being placed within the busy museum world proved to be effective only after the intern accepted a collaborative visitor-centered mindset, involving a focus on the visitor and their connection to the object, collaboration across the entire staff, a certain level of risk-taking, and evaluation. The intern urges museum educators and curators willing to accept the visitor-centered approach to collaborate together as they look for new ways for visitors to experience museums.